Pemberdayaan Kelompok Tani Ara Rezeki untuk Memanfaatkan Limbah Kulit Kopi Arabika menjadi Produk Minuman Teh - Syahirman, Hakim; Nugrahawati, Anis; Irfannur, Irfannur; Muliari, Muliari; Irwansyah, Irwansyah (LPPM Umuslim, 2024)
Bener Meriah Regency is one of the central coffee production areas in Aceh Province, especially in Taman Firdaus Village. Coffee bean processing generates waste in the form of coffee husks, which account for approximately 50-60% of the harvest. Therefore, there is a need for innovation to process coffee husks into a delicious coffee husk tea product with high economic value. Consequently, socialization and training activities are required to process coffee husks for target partners who are direct farmers. It is expected that these activities will: 1) increase the income of the community, especially partner groups, 2) become an alternative for partner groups to utilize coffee husks as a product with high economic value, and 3) cultivate an entrepreneurial spirit among partner groups for products produced through the utilization of Arabica coffee husks.